Systematic characterization of chemical constituents in Mahuang decoction by UHPLC tandem linear ion trap‐Orbitrap mass spectrometry coupled with feature‐based molecular networking. Issue 14 (29th May 2021) - Chen, Ling; Yao, Changliang; Li, Jiayuan; Wang, Jing; Yao, Shuai; Shen, Shijie; Yang, Lin; Zhang, Jianqing; Wei, Wenlong; Bi, Qirui; Guo, De‐an
Abstract: Comprehensive characterization of traditional Chinese medicine prescriptions has long been a hurdle due to the chemical complexity and the lack of analytical tools. Mahuang decoction is a well‐known traditional Chinese medicine prescription widely used for sweating and relieving the exterior, relieving cough and asthma, but it was insufficiently chemically scrutinized. In this study, the chemical component information of Mahuang decoction was investigated by ultrahigh‐performance liquid chromatography tandem linear ion trap‐Orbitrap mass spectrometry. A new data processing tool, feature‐based molecular networking, was introduced for grouping and elucidating the compounds. In this way, 156 chemical components were identified or tentatively characterized, including alkaloids, triterpenoid saponins, flavanone‐ O ‐glycosides, flavone‐ C ‐glycosides, and procyanidins. Thus, this research provides a solid foundation for further development of Mahuang decoction, and the adopted method is expected to be applied to other traditional Chinese medicine prescriptions.